2022
DOI: 10.1101/2022.11.15.516562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PTEX helps efficiently traffic haemoglobinases to the food vacuole inPlasmodium falciparum

Abstract: A key element of Plasmodium biology and pathogenesis is the trafficking of ~10% of the parasite proteome into the host red blood cell (RBC) it infects. To cross the parasite-encasing parasitophorous vacuole membrane, exported proteins utilise a channel-containing protein complex termed the Plasmodium translocon of exported proteins (PTEX). PTEX is obligatory for parasite survival, both in vitro and in vivo, suggesting that at least some exported proteins have essential metabolic functions. However, to date onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…PfGBP130, a known exported soluble protein (Jonsdottir et al, 2023;Perkins, 1988), was detected in the EqtII SN; PfSERA5, a soluble protein which localises in the PV of schizonts (Blackman, 2008;Jonsdottir et al, 2023), was enriched in the Sap SN; parasite cytosolic protein PfHSP70-1 was found mainly in the TX-100 SN. PfSTART1 was almost only detected in the TX100 fraction, indicating that it was either within the parasite, and/or associated with membranes.…”
Section: Pfstart1 Expression Processing and Localisation In Schizonts...mentioning
confidence: 99%
See 1 more Smart Citation
“…PfGBP130, a known exported soluble protein (Jonsdottir et al, 2023;Perkins, 1988), was detected in the EqtII SN; PfSERA5, a soluble protein which localises in the PV of schizonts (Blackman, 2008;Jonsdottir et al, 2023), was enriched in the Sap SN; parasite cytosolic protein PfHSP70-1 was found mainly in the TX-100 SN. PfSTART1 was almost only detected in the TX100 fraction, indicating that it was either within the parasite, and/or associated with membranes.…”
Section: Pfstart1 Expression Processing and Localisation In Schizonts...mentioning
confidence: 99%
“…Proteinase K protection assay. To further determine the localisation of PfSTART1 in schizonts, we conducted a proteinase K protection assay (Jonsdottir et al, 2023). Percollpurified schizonts were washed in PBS+PI, and lysed in 10x the pellet volume of EqtII (to achieve 100% hemolysis) for 10 min at 37°C.…”
Section: Differential Lysis Assaymentioning
confidence: 99%